Transformasi Pendidikan Islam di Kota Pontianak: Kajian Historis Yayasan Perguruan Islamiyah - Nur Izzaturohmah; Helva Zurayah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the historical transformation and the role of the Yayasan Perguruan Islamiyah in shaping the Islamic education system in Pontianak, particularly in maintaining Islamic values amid the dynamics of contemporary education. This study employs a qualitative approach using a case study method. Data were collected through in-depth interviews with foundation administrators, school principals, teachers, students, and history lecturers, and were supported by observation and documentation studies. The research was conducted in July 2025. Data analysis followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, with triangulation techniques used to ensure data validity. The findings indicate that Yayasan Perguruan Islamiyah plays a pioneering role in modern Islamic education through its transformation from traditional religious study circles into a formal education system. In addition, the foundation functions as an agent of social transformation by promoting inclusive education, particularly for women, and contributes to producing educated Muslim generations through the integration of faith, knowledge, piety, and culture. However, the institution faces structural challenges, including a decline in student enrollment due to competition with public schools and limited financial resources. Islamic educational institutions need to strengthen their value-based identity while also innovating in curriculum and educational management to remain relevant to contemporary developments.